A modified hard-templating for hollow mesoporous silica nanoparticles with suitable particle size and shortened synthesis time - Nguyen, Ngoc Hoi; Nguyen, Cuu Khoa; Nguyen, Dai Hai (Vietnam Journal of Science and Technology, 2024)
Hollow mesoporous silica nanoparticles (HMSN), a member of mesoporous silica family synthesized mainly with hard-templating method, has gained great interest in pharmaceutical applications due to their impress characteristics such as good biocompatibility, large specific surface area and pore volume, controllable particle size, large cavity for cargo loading, and flexible surface functionalization possibilities. However, controlling the optimal particle size and shortening the synthesis time have been the issues of HMSN synthesis that needed to be improved. In this study, HMSN was synthesized using hard-templating with some modifications to shorten the synthesis time and adjust the particle size to nearly 100 nm. The obtained HMSN particles showed high uniform morphology as spheres with hollow core-mesoporous shell structure, having the particle diameter of about 90 nm, the hollow diameter of about 68 nm, and the mesoporous shell thickness of about 11 nm. The total time for the main reactions was shortened by more than half from 21 hours to 9 hours. Additionally, MTT assays revealed that the synthesized HMSN was biocompatible material. This modified hard-template method with shorter synthesis time and nearly 100 nm obtained particle diameter would be meaningful for scientific research and industrial scale production.